2013
DOI: 10.1136/oemed-2013-101717.102
|View full text |Cite
|
Sign up to set email alerts
|

102 Occupational asbestos exposure and risk of pleural mesothelioma, lung and laryngeal cancer in the prospective Netherlands Cohort Study

Abstract: Objectives Although asbestos research has been ongoing for decades, there are remaining questions regarding cancer risk associated with low exposure and cancer subtypes, the influence of potential confounders, and the interaction between asbestos and smoking. We addressed these questions by studying the association between occupational asbestos exposure and pleural mesothelioma, lung and laryngeal cancer in the prospective population-based Netherlands Cohort Study (NLCS). Methods The NLCS includes 58279 men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Among the cohort studies, 2 accounted for exposure to smoking and alcohol when determining the RR and hazard ratio in their patient populations. 25,27 Relative risk in the study by Purdue et al 25 was 1.8 (95% CI, 0.8-4.3) and the hazard ratio in the study by Offermans et al 26 was 6.36 (95% CI, 2.18-18.53). Purdue et al 25 described only 2 patients with laryngeal cancer as a result of asbestos exposure, but concluded that there is an association between asbestos exposure and laryngeal cancer, while the study by Offermans et al 26 did not find any correlation.…”
Section: Cohort Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Among the cohort studies, 2 accounted for exposure to smoking and alcohol when determining the RR and hazard ratio in their patient populations. 25,27 Relative risk in the study by Purdue et al 25 was 1.8 (95% CI, 0.8-4.3) and the hazard ratio in the study by Offermans et al 26 was 6.36 (95% CI, 2.18-18.53). Purdue et al 25 described only 2 patients with laryngeal cancer as a result of asbestos exposure, but concluded that there is an association between asbestos exposure and laryngeal cancer, while the study by Offermans et al 26 did not find any correlation.…”
Section: Cohort Studiesmentioning
confidence: 90%
“…Two studies 18,23 reported an increased risk of developing laryngeal cancer with asbestos exposure, while the remaining cohort studies did not. [19][20][21][22]24,27…”
Section: Cohort Studiesmentioning
confidence: 99%
“…Asbestos is the best‐known example of this phenomenon. Asbestos frequently shows at least a supra‐additive interaction with smoking in determining lung cancer risk 24–28 . Several large studies addressing the lung cancer risk among silica‐exposed workers have been completed in the past decade, generally suggesting a supra‐additive effect with cigarette smoke 29–33 .…”
Section: Evidence‐basis For This Statementmentioning
confidence: 99%